Genetic transformation of potato (Solanum tuberosum L.) using a binary Agrobacterium tumefaciens vector with patatin promoter class I - Kovalenko, P.G.; Yefimenko, I.M.; Schuman, N.V.; Medvedeva, T.V.; Gazaryan, K.G.; Galkin, A.P. (Биополимеры и клетка, 1996)
Kanamycin resistant plants of S. tuberosum L. (in vitro-grown) cv. Zarevo were obtained from tlie cocultivated microtubers with A. tumefaciens. A disarmed binary vector systems containing the neomycin phosphotransferase (NPT II) gene as selectable marker and chloramphenicol acetyltransferase (CAT), as a reporter gene, under control of new patatin promoter class I were utilized. In vitro grown minitubers discs were used as sources of explants to produce transgenic plants on selective medium containing 100 μg/1 kanamycin and CAT enzyme activities were detected. Стійкі до канаміцину рослини-регенеранти картоплі S. tuberosum L (сорту Зарево) було отримано шляхом культивування мінібульб зі штамом A. tumefaciens. Використано бінарну векторну систему, яка містила ген неоміиинфосфотрансферази (НФТ II) як селективний маркер та репортерний ген хлорамфеніколацетилтрансферази (CAT) під контролем промотора пататииу класу 1. Трансгенні рослини було одержано з трансформованих мінібульб картоплі на селективному поживному середовищі з концентрацією канаміцину 100 мл/л. Було підтверджено активність CAT. Устойчивые к канамицину растения-регенеранты картофеля S. tuberosum L (сорта Зарево) получены культивированием миниклубней со штаммом A. tumefaciens. Использована векторная система, содержащая ген неомицинфосфотрансферазы (НФТ II) как селективный маркер и репортерный ген хлорамфениколацетилтрансферазы (CAT) под контролем промотора пататина класса I. Трансгенные растения получены из трансформированных миниклубней картофеля на селективной питательной среде с концентрацией канамицина. 100 мл/л. Была экспериментально подтверждена активность CAT.